La présence italienne en Provence à partir de la fouille archéologique de cimetières (xvie-xxe s.) - Anne Richier; Nicolas Weydert (Diasporas: Circulations, Migrations, Histoire)
Italians migrated to Provence long before the Industrial Revolution and the inflow of transalpine workers in the 19th and 20th centuries. Recent archaelogical excavations conducted in two cemeteries in La Ciotat and Marseille (both cities with a strong Italian presence) allow one to question identity, memory, the importance of origins and forgetting through death. While archaelogy rarely addressed these societal issues in any other way than through material culture, the recent nature of these two cemeteries (16th-20th centuries) allow for a broader discussion across the social sciences.